2019
DOI: 10.1002/ece3.4980
|View full text |Cite
|
Sign up to set email alerts
|

Implications of shared predation for space use in two sympatric leporids

Abstract: Spatial variation in habitat riskiness has a major influence on the predator–prey space race. However, the outcome of this race can be modulated if prey shares enemies with fellow prey (i.e., another prey species). Sharing of natural enemies may result in apparent competition, and its implications for prey space use remain poorly studied. Our objective was to test how prey species spend time among habitats that differ in riskiness, and how shared predation modulates the space use by prey species. We studied a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 87 publications
(196 reference statements)
0
7
0
Order By: Relevance
“…Interspecific competition occurs when two or more species share scarce resources resulting in negative effects on physiology, growth, and survival of at least one of them [ 80 , 81 ]. Dietary overlap has been reported between ungulates and lagomorphs [ 54 , 81 , 82 , 83 , 84 , 85 ], with the latter often forced by larger herbivores to use suboptimal areas [ 84 ]. The roe deer was the only cervid occurring in our study area, apart from the rare fallow deer Dama dama [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interspecific competition occurs when two or more species share scarce resources resulting in negative effects on physiology, growth, and survival of at least one of them [ 80 , 81 ]. Dietary overlap has been reported between ungulates and lagomorphs [ 54 , 81 , 82 , 83 , 84 , 85 ], with the latter often forced by larger herbivores to use suboptimal areas [ 84 ]. The roe deer was the only cervid occurring in our study area, apart from the rare fallow deer Dama dama [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The European brown hare evolved in predator-rich ecosystems, including a rich community of native and introduced mesocarnivores, as well as with several potential competitors, particularly in Europe [ 84 , 85 ]. In Italy, where our research was conducted, the hare is reported as a prey species for a large number of small and medium-sized carnivores including at least eight mustelids, four canids, and two felid species [ 30 , 86 ], as well as a potential competitor of several species of ungulates and lagomorphs [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…Astete et al., 2016; Rich et al., 2017; Rota et al., 2016). Spatial interactions between predator and prey have been examined using stratified random or systematic deployment of multiple cameras, which allows for detailed analyses of patterns of avoidance, association, co‐occurrence and fine‐scale space use (Rota et al., 2016; Weterings et al., 2019). Camera traps have also been implemented to examine how predators and prey partition time (Frey et al., 2017) and to quantify the degree of temporal overlap between two species (Ridout & Linkie, 2009) over daily (Monterroso, Alves, & Ferreras, 2013), monthly (e.g.…”
Section: Observational Applications Of Camera Traps To Predator–prey mentioning
confidence: 99%
“…As for most herbivorous mammals, the trade‐off between predator avoidance (e.g. Knauer et al 2010, Zaccaroni et al 2012, Weterings et al 2016, 2019, Mayer et al 2020b) and access to high‐quality food resources (Weterings et al 2018) may underlie spatiotemporal adaptations in this lagomorph. Although we confirm that the hare is an open area and farmland specialist, the proportional use of most habitat types and seasonal modulations in activity suggests considerable plasticity in its use of space and time.…”
Section: Discussionmentioning
confidence: 99%